Bacterial and viral contamination of breathing circuits after extended use – an aspect of patient safety?. Issue 9 (29th July 2016) - Dubler, S.; Zimmermann, S.; Fischer, M.; Schnitzler, P.; Bruckner, T.; Weigand, M. A.; Frank, U.; Hofer, S.; Heininger, A.
Abstract : Background: In the past, anaesthetic breathing circuits were identified as a source of pathogen transmission. It is still debated, whether breathing circuits combined with breathing system filters can be safely used for more than 1 day. The aim of this study was to evaluate the transmission risk of bacteria and also viruses via breathing circuits after extended use. Methods: The inner and outer surface of 102 breathing circuits used for 1 day and of 101 circuits used for 7 days were examined for bacteria and viruses. Additionally, 10 and 20 breathing circuits each were examined after use on patients with pulmonary virus infection and with multidrug‐resistant organism (MDRO) colonisation/infection respectively. Bacteria were detected by standard microbiological procedures; PCR techniques were applied for herpes simplex virus, cytomegalovirus, influenza, parainfluenza and respiratory syncytial virus. Results: Endoluminal bacterial contamination of breathing circuits remained unchanged after 7‐day vs. 1‐day use (5.9% vs. 7.8%) [CI95%: −0.0886–0.0506, pnon‐inferiority 0.0260]. Only outside surface contamination with bacteria belonging to environmental species or human flora increased (16.8 vs. 6.9%) [CI 95%: 0.0118 – 0.1876, pnon‐inferiority 0.8660]. Viruses occurred on the patient side, but not in breathing circuits. No MDRO occurred in the 20 circuits after use on patients harbouring such germs. Conclusion: Endoluminal contamination of breathing circuits with bacteria did not increase after extended use. No viruses were detected in the breathing circuits using filters. Based on our results, the extended use of ABC without exceptions appears safe, if a high level of anaesthesia workplace cleaning is secured.